Description of Work Instructions as part of the Mechanical Hazard Risk Control in a Construction Company - Sabhinaya Vanyaska Gitawangi; Y. Denny A. Wahyudiono (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: The construction sector contributes the largest number of accident cases in Indonesia with an average incidence percentage of 32% each year. PT. WIKA Beton PPB Pasuruan uses sophisticated equipment to produce its products. To control the risk of mechanical hazards, the company has work instructions for each stage of the production process. This research aimed to provide an overview of how the work instructions are an effort to control the risk of mechanical hazards in the box pile production process at PT. WIKA Beton PPB Pasuruan. Method: This research was a descriptive study with a qualitative approach. The data collection technique used secondary data. The data used came from the company documents that included the IBPR-P document, Procedure document, and Work Instructions. Result: The mechanical hazards found in the production process of the box piles included being hit by a mold/product due to a broken sling, a PC Strand breaking during stressing, PC Strand punctured limbs, and the pile of products collapsing. The control of these four mechanical hazards was found in the Long Line Non-Turning Production Reinforcement Assembly Work Instructions, the Long Line Non-Turning Production Prestress Iron Drawing Work Instructions, and the Long Line Non-Rotating Production Product Stacking Work Instructions. Conclusion: In the work instruction documents, there were specific explanations of the work stages that relate the risk of mechanical hazards in the box pile production process. Implementing Work Instructions as a form of mechanical hazard control can reduce the level of potential hazard to a low risk level.